PLD.23 Management of transverse and unstable lie at term. (9th June 2014) - Szaboova, R; Sankaran, S; Harding, K; Shennan, A
Abstract : Aims: To determine current practice and outcomes in women admitted to antenatal ward with diagnosis of transverse or unstable lie. Background: Fetal lie (other than longitudinal) at term may predispose to prolapse of cord or fetal arm and uterine rupture. Local guidelines recommend admission at 37+0 (RCOG guidelines after 37+6 weeks) but give no specific recommendations regarding further management. Methods: A retrospective study was conducted at St Thomas' Hospital, London from 2009–2012 of all women admitted with unstable/transverse lie. The diagnosis was based on ultrasound examination. Women with placenta praevia and non-singleton deliveries were excluded. Results: Study included 198 cases of unstable/transverse lie. 58% were admitted before 38 weeks. The average length of admission was 7 days (IQR 4–11). There were no cases of cord prolapse or need for an immediate caesarean section from the antenatal ward. 73% of women had a caesarean section at a median gestation of 39+1 weeks (IQR 38+4 – 40+2) although almost half of these (41%) had a cephalic presentation at the time of elective caesarean sections. None of these had an absolute indication for Caesarean section. Discussion and conclusions: The diagnosis of unstable/transverse lie leads to a prolonged inpatient stay and a high Caesarean section rate. From our study and the evidence from the available literature, we recommend delaying admission until at least 38 weeks and awaiting spontaneous version. Future research should focus on the safety of outpatient management with consideration of utilising techniques such as cervical length and fetal fibronectin.